Learning Indonesian Struggle History in Bukittinggi Through the Tridaya Eka Dharma Museum Collections - Hasfera, Dian; Rahmi, Lailatur; Husna Zalmi, Fadhila Nurul; M. Fadli; Safitri, Riski (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The Tridaya Eka Dharma Museum commonly known as the Struggle Museum saves many weapons from the soldiers of the Emergency Government of the Republic of Indonesia (PDRI) and the Revolutionary Government of the Republic of Indonesia (PRRI). Besides that, the museum also displays weapons captured from the war in East Timor. The Tridaya Eka Dharma Museum located in Bukitinggi City. Bukittinggi was chosen as the location for the museum because this city was once the capital of Sumatra province and the capital of the Republic of Indonesia during the PDRI era. Therefore, Bukittinggi has a rich history in Indonesia's struggle for independence, and this museum plays an important role in preserving and commemorating that history. This research was carried out considering that the function of museums for knowledge requires action so that they are not neglected and abandoned by the next generation. Referring to the condition of the younger generation called as Gen Z generation who are more dependent on sources of information via gadgets and the internet, this research needs to be carried out, name to provide an overview of the condition that museums belong to all generations, lest the museum ecosystem itself stops in one generation. This is creating a huge gap between one generation to the next generation. It is hoped that this research will be able to contribute to and maximize the function of museums which act as institutions that protect, develop, utilize collections, and communicate them to the public. The purpose of this research is to find out the collection of objects in the Tridaya Eka Dharma Museum and explain the use of the Tridaya Eka Dharma Museum in learning the History of Indonesian Independence. The research method that will be used as a source of historical learning is the descriptive method.